Teori Naẓm Perspektif Abdul Qahir al-Jurjani: Posisinya dalam Keilmuan Bahasa Arab dan Spesifikasinya di Antara Teori-Teori Sebelumnya - Muhammad Al-Mubassyir; Abdul Wahab Naf'an; Bahrul Ulum (Uktub)
Following the growth and development of Arabic linguistic sciences, the pioneering of the science of balaghah which was motivated by the i’jāz of the Qur’an began to be discussed among scholars. This discussion started from the point of the Qur’anic miracle, which often led to conflicting views among them. Among the intriguing topics that captured the attention of scholars and critics at the time was the theory of naẓm, which was regarded as the miraculous aspect of the Qur’anic language and later associated with the thoughts of Abdul Qahir al-Jurjani (d. 471 AH). However, this theory was discussed even before al-Jurjani. Al-Jurjani continued, refined, and completed the discussion of what had been initiated by his predecessors. By examining al-Jurjani’s works, Dalāil al-I’jāz, and referring to Ahmad Darwisy and Izzah Jadwa's book, al-Balāgah al-Qur’ānīyah: Dirāsah fī Jamāliyāt al-Naṣṣ al-Qur’ānī, combined with several other sources, this article explores the theory of naẓm from Abdul Qahir al-Jurjani’s perspective, its position within Arabic linguistic sciences, and its specifics in comparison to the naẓm theories discussed by some of his predecessors. The study concludes that Abdul Qahir al-Jurjani’s perspective on the theory of naẓm is a structured arrangement or tarkīb composed through the selection of detailed, specific, and proportional components based on its syntactical meanings (ma’ānī naḥwīyah) which refer to the meanings in the mind (ma’ānī nafsīyah) that are its objectives. This arrangement process is carried out through two methods: ikhtiyār (selection) and ta’līf (composition).